2022
DOI: 10.5551/jat.rv17061
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and Cardiovascular Diseases in Progeroid Syndromes

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) and Werner syndrome (WS) are two of the representative genetic progeroid syndromes and have been widely studied in the field of aging research. HGPS is a pediatric disease in which premature aging symptoms appear in early childhood, and death occurs at an average age of 14.5 years, mainly due to cardiovascular disease (CVD). Conversely, WS patients exhibit accelerated aging phenotypes after puberty and die in their 50s due to CVD and malignant tumors. Both diseases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…In addition, in a recent autopsy of a patient with WS who died at age 76, there were almost no atherosclerotic changes in the cerebral vessels and no stenosis in the coronary arteries [ 7 , 12 ]. A number of other recent case reports have also shown that atherosclerotic changes were absent or slightly present [ 13 , 14 ]. These findings suggest that atherosclerotic diseases are being controlled in WS.…”
Section: Discussion/conclusionmentioning
confidence: 88%
“…In addition, in a recent autopsy of a patient with WS who died at age 76, there were almost no atherosclerotic changes in the cerebral vessels and no stenosis in the coronary arteries [ 7 , 12 ]. A number of other recent case reports have also shown that atherosclerotic changes were absent or slightly present [ 13 , 14 ]. These findings suggest that atherosclerotic diseases are being controlled in WS.…”
Section: Discussion/conclusionmentioning
confidence: 88%
“…A clinical trial with nicotinamide riboside, a precursor of NAD, which may be effective for intractable ulcers, sarcopenia, and ASCVD, is investigating the safety and efficacy in patients with Werner syndrome [ 66 ]. Using state-of-the-art technologies, such as genome, transcriptome, and epigenome analyses [ 67 ], study of the generation of iPS cells from patients with Werner syndrome and the correction of the WRN gene by the CRISPR/Cas9-mediated methods [ 68 ] will create new treatments for patients with Werner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These may implicate common vascular changes in affected brain regions in CS and elderly. Atherosclerosis appears to be an atypical feature in CS patients ( Hayashi et al, 2012 ) in contrast to HGPS and WS ( Kato and Maezawa, 2022 ). Recent studies in CS mouse model, Csa−/−Xpa−/− , found no changes in isolated endothelial cells or aorta ( Kajitani et al, 2021 ) suggesting rather non-cell autonomous effects ( Table 1 ) as an underlying cause for brain vascular defects thereby favoring the hypothesis of neural-centric view of aging in CS ( Figure 3 ).…”
Section: Progeroid Syndromes: Accelerated Aging Models Of Characteris...mentioning
confidence: 99%